Stereoinversion of R‐Configured Secondary Alcohols Using a Single Enzymatic Approach. Issue 36 (27th September 2018) - Musa, Musa M.; Karume, Ibrahim; Takahashi, Masateru; Hamdan, Samir M.; Ullah, Nisar
Abstract: Here, we achieved a single‐enzymatic stereoinversion of R ‐configured alcohols to their corresponding S enantiomers in high percent conversion and high enantioselectivity. A single mutant of Thermoanaerobacter pseudoethanolicus secondary alcohol dehydrogenase (TeSADH) oxidized R alcohols to their corresponding ketones under conditions that allow selectivity mistakes and then reduced them under stereoselective conditions to generate the corresponding S ‐configured alcohols. The success of this stereoinversion relies on controlling the stereoselectivity of the oxidation and the reduction reactions by varying the amounts of acetone and 2‐propanol, respectively. Furthermore, the deployment of the TeSADH mutants W110A and W110G led to stereoinversion of enantiopure R alcohols to their S enantiomers in medium to high enantiomeric excess (up to >99% ee ). The disclosed approach of single enzymatic stereoinversion presents a biocatalytic alternative to Mitsunobu inversion reaction. Abstract : A stereoinversion approach of R ‐configured secondary alcohols catalyzed by a single alcohol dehydrogenase is achieved through a non‐stereoselective oxidation to the corresponding ketones, followed by a stereoselective reduction catalyzed by the same alcohol dehydrogenase to produce the S ‐configured alcohols. This single enzymatic stereoinversion approach presents a biocatalytic alternative to the laborious Mitsunobu inversion reaction.